Not Breathing During the Approach Phase Ameliorates Freestyle Turn Performance in Prepubertal Swimmers - Faelli, Emanuela; Strassera, Laura; Ottobrini, Sara; Ferrando, Vittoria; Bisio, Ambra; Puce, Luca; Panascì, Marco; Lagorio, Cesare; Ruggeri, Piero; Bove, Marco (Frontiers in Sports and Active Living, 2021)
This study compared the effects of two breathing conditions during the freestyle turn approach phase in swimmers. Thirty-four prepubertal swimmers (mean±SD: 10.59±0.97 years) were divided into two groups: No Breath (NB), not breathing at the last stroke, and Breath Stroke (BS). Swimmers performed three turns with 5 min of rest between the repetitions. Kinematic parameters were recorded with two underwater and two surface cameras. Total turn time (NB: 9.31±1.34 s; BS: 10.31±1.80 s; p=0.049), swim-in time (NB: 3.89±0.63 s; BS 4.50±0.79 s; p=0.02) and rotation time (NB: 2.42±0.29 s; BS: 3.03±0.41 s; p=0.0001) were significantly shorter and swim-in distance (NB: 0.70 [0.58,0.77] m; BS: 0.47 [0.34,0.55] m; p=0.0001), glide distance (NB: 1.06±0.21 m; BS: 0.70± 0.20 m; p=0.0001) and surfacing distance (NB: 1.79 [1.19,2.24] m; BS: 1.18 [0.82,1.79]m; p=0.043) were significantly longer in NB than in BS. Moreover, speed-in (NB: 1.04±0.14 m/s; BS: 0.93±0.14 m/s; p=0.031) and push-off speed (NB: 2.52± 0.30 m/s; BS: 1.23±0.20 m/s; p=0.001) were significantly higher in NB than in BS. Swim-in time was positively and negatively correlated with rotation time and glide distance, respectively, whilst negative relationships between total turn time and swim-in distance, total turn time and surfacing distance and total turn time and speed-in were found. Our study showed that in prepubertal swimmers not breathing at the last stroke during the approach phase positively affected kinematic parameters of the turn, allowing to approach the wall faster, rotate the body quicker, increase push-off speed, reduce turn execution time, thus improving overall turn performance.